2017
DOI: 10.1021/acsami.7b07981
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Mediated Destruction of Cancer Using the Cell’s Own Hydrogen Peroxide

Abstract: A novel reduced iron metal-organic framework nanoparticle with cytotoxicity specific to cancer cells is presented. This nanoparticle was prepared via a hydrothermal method, reduced using hydroquinone, and finally conjugated with folic acid (namely, rMOF-FA). The synthesized nanoparticle shows the controlled release of iron in an acidic ex-vivo environment. Iron present on the rMOF-FA and released into solution can react with high levels of hydrogen peroxide found specifically in cancer cells to increase the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 65 publications
1
99
0
Order By: Relevance
“…[21] Thec ellular uptake efficiency and uptake pattern were tested in 4T1 cells by applying various endocytosis inhibitors and treating cells at 4 8 8C. [22] As shown in Figure 3c,t here was very faint fluorescence observed in the control and laser group.T he fluorescence slightly increased in the NMOF + Laser group,indicating that moderate amounts of ROS were generated because of the naturally occurring GSH inducing NMOF degration and activation of TCPP.T he difference in fluorescence for the TCPP + Laser group and NMOF + Laser group could be attributed to the GSH depletion of the NMOF.T he fluorescence greatly enhances with DHA in the NMOF,b ecause of the ROS generation from Fe 2+ and DHA, as well as the enhanced GSH depletion caused by cycling reaction between Fe 3+ and Fe 2+ .S ince CaCO 3 had no effect on the ROS generation, the fluorescence intensity exhibited no obvious difference from the NMOF@DHA + Laser group.T he comparison of ROSg eneration efficiency in normal and cancer cells indicated that the environment of cancer cells benefited from ROS generation (see Figure S17). Theb io-TEM images also showed that nanoplatforms were efficiently endocytosed into the cells (see Figure S16).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…[21] Thec ellular uptake efficiency and uptake pattern were tested in 4T1 cells by applying various endocytosis inhibitors and treating cells at 4 8 8C. [22] As shown in Figure 3c,t here was very faint fluorescence observed in the control and laser group.T he fluorescence slightly increased in the NMOF + Laser group,indicating that moderate amounts of ROS were generated because of the naturally occurring GSH inducing NMOF degration and activation of TCPP.T he difference in fluorescence for the TCPP + Laser group and NMOF + Laser group could be attributed to the GSH depletion of the NMOF.T he fluorescence greatly enhances with DHA in the NMOF,b ecause of the ROS generation from Fe 2+ and DHA, as well as the enhanced GSH depletion caused by cycling reaction between Fe 3+ and Fe 2+ .S ince CaCO 3 had no effect on the ROS generation, the fluorescence intensity exhibited no obvious difference from the NMOF@DHA + Laser group.T he comparison of ROSg eneration efficiency in normal and cancer cells indicated that the environment of cancer cells benefited from ROS generation (see Figure S17). Theb io-TEM images also showed that nanoplatforms were efficiently endocytosed into the cells (see Figure S16).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…A fluorescent probe 2',7'-dichlorofluorescein diacetate (DCFH-DA)was chosen to assess intracellular ROSproduction. [22] As shown in Figure 3c,t here was very faint fluorescence observed in the control and laser group.T he fluorescence slightly increased in the NMOF + Laser group,indicating that moderate amounts of ROS were generated because of the naturally occurring GSH inducing NMOF degration and activation of TCPP.T he difference in fluorescence for the TCPP + Laser group and NMOF + Laser group could be attributed to the GSH depletion of the NMOF.T he fluorescence greatly enhances with DHA in the NMOF,b ecause of the ROS generation from Fe 2+ and DHA, as well as the enhanced GSH depletion caused by cycling reaction between Fe 3+ and Fe 2+ .S ince CaCO 3 had no effect on the ROS generation, the fluorescence intensity exhibited no obvious difference from the NMOF@DHA + Laser group.T he comparison of ROSg eneration efficiency in normal and cancer cells indicated that the environment of cancer cells benefited from ROS generation (see Figure S17).…”
Section: Angewandte Chemiementioning
confidence: 63%
“…The results further demonstrated that Co 2+ ions acted as the necessary Fenton‐like reaction catalyst driving generation •OH radicals (Figure S5, Supporting Information). In addition, the generation of •OH was further evaluated at pH 5.0 using 3,3′,5,5′‐tetramethylbenzidine (TMB), which is oxidized by •OH to form ox‐TMB . As shown in Figure d, the UV–vis absorption spectra revealed that the production of ox‐TMB was dependent on the concentration of CaO 2 @DOX@ZIF‐67.…”
Section: Methodsmentioning
confidence: 99%